Empyema Thoracis in children: A Five-Year Analysis from a Tertiary Care Center in Eastern Nepal - Kafle, Shyam Prasad; Koirala, Namu; Ahmad, Eqtedar; Rauniyar, Lalan Prasad; Bhatta, Mukesh (Journal of Nepal Paediatric Society, 2022)
Introduction: Complicated community-acquired pneumonia resulting in empyema thoracis remains the largest single cause of morbidity and mortality worldwide in children. This study was carried out to evaluate the clinical profile, associated complications and outcome of empyema thoracis in children. Methods: A retrospective study was conducted in the Department of Paediatrics at a tertiary care center in Eastern Nepal. A total of 106 children were managed with the diagnosis of complicated pneumonia with effusion or empyema thoracis from March 2017 to February 2021 (Five years). Only those patients who had clinico-radiological evidence of pleural effusion or empyema thoracis and received treatment with or without intercostal chest tube drainage (ICD) as the initial procedure were enrolled in the study. Besides supportive treatments and antibiotics; streptokinase was instilled intrapleurally in all the patients for three days. Patients who did not respond underwent VATS / decortication. Results: Majority of the children (60.19%) were below five years of age and were males (73.58%). Majority (55.67%) had a right-sided pleural effusion and fever was the predominant symptom (55.66%) at presentation. The pleural fluid culture was sterile in more than half (55.66%) of the patients with Staphylococcus aureus grown in 33.96%. The three most common complications were subcutaneous emphysema, thickened pleura, and pyo-pneumothorax. The success rate of medical management was 83.96% and the mortality was low (2.84%). Conclusions: The success rate of conservative management with antimicrobial therapy, intercostal drainage and fibrinolytics in this study was high (83.96%) with no major adverse effects of fibrinolytic therapy in empyema thoracis.